PENGARUH KEPEMIMPINAN KEPALA SEKOLAH BERBASIS BUDAYA LITERASI DAN KOMPETENSI SUPERVISI TERHADAP KINERJA GURU - Badariah , Bai; Hidayat , Sholeh; Hilaliyah, Tatu (Program Studi PGMI, 2025)
This research is motivated by the fact that in schools in the Koroncong sub-district there are several teachers who still have difficulties in designing learning tool planning such as compiling semester programs, compiling annual programs, compiling basic competency standards and core competencies, teachers have difficulty in compiling teaching materials, teachers are weak in mastering classroom management as well as the use of IT in learning and the low literacy culture as a reference to continue renewing themselves according to the times. Teachers have a strategic role in improving the quality of education. Therefore, in order for teacher performance to be more optimal, of course, the influence of supervision of the principal as a leader in the school must exist. This research was conducted with the aim of determining the influence of the leadership of school principals based on literacy culture and the competence of the supervision of the head of the school on teacher performance. Literacy culture-based principal leadership is a norm of behavior for school principals that is used to mobilize all subordinates (teachers and education staff) to be able to work actively and creatively which is associated with the development of literacy movement programs in order to achieve common goals. Supervision competence is a number of knowledge and skills of school principals in conducting coaching and supervision to help teachers and their staff to be able to carry out and improve their performance in learning at school. The method used is a correlational research method. This research was conducted on elementary school teachers in Koroncong district. The sampling technique uses the clutser random sampling technique. The data collection technique uses questionnaire or questionnaire instruments, then analyzed in depth by paying attention to various theories, expert opinions as well as references from previous studies. The results of this study show that there is an influence of principal leadership based on literacy culture and principal supervision competence on teacher performance. The principal as the main leader who has the authority to manage the school organization should be able to provide motivation, direction and supervision to teachers so that their performance is better.